Presentation, treatment and outcome of long‐bone fractures in pet rabbits (Oryctolagus cuniculus). (28th November 2019) - Garcia‐Pertierra, S.; Ryan, J.; Richardson, J.; Koterwas, B.; Keeble, E.; Eatwell, K.; Clements, D. N.
Abstract : Objectives: To describe the incidence, aetiology, characteristics, assessment, management and outcome of long‐bone fractures in rabbits presenting to a single institution. Materials and Methods: Medical records of pet rabbits diagnosed with long‐bone fractures over a 12‐year period were analysed. Patient signalment, fracture aetiology, fracture location, fracture description, time from fracture occurrence to veterinary presentation, fixation method, postoperative complications, clinical outcome and follow‐up were recorded. Results: Twenty‐eight pet rabbits that sustained 30 fractures were included in the study [femoral (n=12), tibial (n=6), metacarpal/metatarsal/phalangeal (n=5), radial and ulnar (n=4) and tarsal (n=3)]. Twenty‐one (75%) of the rabbits were less than 2 years of age, including seven (25%) under 6 months of age. Twenty‐five fractures had no identifiable cause and five were traumatic. Only one fracture was open. Surgical stabilisation was performed in 22 fractures, four were non‐surgically managed, two had the affected limb amputated, one underwent digital amputation and one was euthanased. Postoperative complications occurred in nine fractures [major (n=6), minor (n=3)]. The frequency of complications or attainment of a functional recovery was not notably different between the different methods of fixation. Overall, 24 rabbits recovered, two were euthanased and four underwent limb amputation. Clinical Significance: Fractures in rabbits typically occur in young animals and they usually lack an obvious aetiology. The majority of the rabbits treated achieved a functional recovery, although the postoperative complication rate was high in fractures treated surgically (41%).